1965
DOI: 10.1161/01.res.17.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pulmonary Vascular Resistance in the Dependent Zone of the Isolated Dog Lung Caused by Perivascular Edema

Abstract: Measurements of the distribution of blood flow in an isolated dog lung made with radioactive xenon showed a great increase in vascular resistance in the dependent zone of the lung in the presence of a raised pulmonary venous pressure in some preparations. Evidence that this increased vascular resistance was caused by perivascular edema consisted of the general correlation with interstitial edema, the regional distribution of the effect, the sensitivity to the arteriovenous pressure difference, the effect of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
2

Year Published

1966
1966
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(42 citation statements)
references
References 24 publications
2
38
0
2
Order By: Relevance
“…The influence of mechanical factors such as interstitial perivascular edema should be discounted, since the hemodynamic situation is quite different from that under which perivascular edema is known to occur (51), and the levels of the left atrial and plasma colloid osmotic pressures, as discussed below, should not allow the increase of interstitial fluid in the lung (52,53).…”
Section: Pulmonary Vascular Distensibilitymentioning
confidence: 99%
“…The influence of mechanical factors such as interstitial perivascular edema should be discounted, since the hemodynamic situation is quite different from that under which perivascular edema is known to occur (51), and the levels of the left atrial and plasma colloid osmotic pressures, as discussed below, should not allow the increase of interstitial fluid in the lung (52,53).…”
Section: Pulmonary Vascular Distensibilitymentioning
confidence: 99%
“…For perfusion, Muir et al (23) found that gross alveolar edema was required for a reduction in local blood flow. Except at extremely low flows and arterial-venous differences (24), the distribution of blood flow in the isolated lung preparation is relatively insensitive to edema (22) (25). In the one preparation (lung 7) with severe edema, lower zone blood volume and flow was reduced relative to that in the middle and upper zones.…”
Section: Introductionmentioning
confidence: 96%
“…Since the bulk flow of water in tissues does follow Starling's law, filtration coefficients have been found to be useful for comparing the permeability characteristics of different tissues (2). Filtration coefficients for the dog lung can be calculated from the data of groups I and II by substitution in Starling's law, assuming that the interstitial fluid pressure (Pif) approaches and exceeds zero as interstitial edema accumulates (23,25). The filtration coefficient, k, is expressed per square centimeter of capillary surface area; the alveolar surface area of the dog, approximately 50 m2 (33), is taken as an estimate of the pulmonary capillary surface area for the dogs of groups I and II, having an average body weight of 14 kg and an average dry lung weight of 23 g. For a (Pif -lrif) of zero, the filtration coefficient calculated from the mean data of group I is 0.12 x 10-8, and from the mean data of group II, 0.26 X 10-ml per second per cm2 per mm Hg AP.…”
Section: Introductionmentioning
confidence: 99%